Efektivitas Metode Ekstraksi Ramah Lingkungan Terhadap Kualitas dan Efisiensi Produksi Fitofarmaka dari Jahe (Zingiber officinale): Kajian Literatur - Ninjaya, Anak Agung Ngurah Gede Aditya; Dewi, Putu Mas Dyani; Dewi, Ni Putu Arya Krisna; Parta, Nyoman Adinda Triana Putri; Dewi, Ni Kadek Santi Maha (Innovative: Journal Of Social Science Research, 2025)
The increasing global demand for phytopharmaceutical products demands innovation in sustainable production processes, especially at the stage of extracting active ingredients from herbal plants such as ginger (Zingiber officinale). This study aims to evaluate the effectiveness of environmentally friendly extraction methods on the quality and efficiency of phytopharmaceutical production from ginger. The study was conducted through a systematic literature review of ten selected articles discussing green extraction methods in the period 2020 to 2025, with one exception for relevant articles outside that period. The methods studied included Ultrasound-Assisted Extraction (UAE), Microwave-Assisted Extraction (MAE), Subcritical Water Extraction (SWE), and Supercritical Fluid Extraction (SFE), considering the type of solvent, operational conditions, and main bioactive compounds such as gingerol and shogaol. The results of the analysis showed that SWE and SFE excel in terms of sustainability and purity of results, while UAE and MAE offer time and energy efficiency. The choice of solvents such as water, ethanol, and CO₂ has been shown to affect the stability of bioactive compounds and the ecological impact of the process. This study confirms that green extraction methods play an important role in ensuring the quality of the extract results while supporting environmentally responsible phytopharmaceutical production. The implications of these results encourage the adoption of sustainable approaches on an industrial scale to strengthen the competitiveness of national herbal products.